Studies on the population of methane-oxidizing bacteria and methane-oxidizing activity in Huangsong rice-field soil - CHEN Zhong-yun; MIN Hang; WU Wei-xiang; CHEN Mei-chi (浙江大学学报. 农业与生命科学版, 2001)
The populations of methane-oxidizing bacteria were analyzed in Huangsong soils with various plant-cover, using Hungate anaerobic technique and chromatographic monitoring method. The results showed that the population of methane-oxidizing bacteria ranged 107-108 cfu/g dried soil with different plant-cover. The various plant-cover on soil seemed to have no significant effect on the population of methane-oxidizing bacteria, but to have noteworthy effect on the methane-oxidizing activity in soil sampies. The variation of the population of methane-oxidizing bacteria had no significant effect on methane oxidation rate in soil. When pure methane was added to tested soil, which had lower activity of methane oxidation, the population of methane oxidizing bacteria and the activity of methane oxidation could be induced to increase obviously. But the time needed up to the highest activity of methane oxidation was various in the tested soils with different plant-cover.